2018
DOI: 10.3389/fpsyg.2018.01364
|View full text |Cite
|
Sign up to set email alerts
|

Utrecht-Management of Identity Commitments Scale: Validation in Spanish University Students

Abstract: The Utrecht-Management of Identity Commitments Scale (U-MICS) has already been validated in nine languages and has had a major scientific impact. Thus, the aim of this study was to validate this instrument in its Spanish version, one of the most important languages in the world. We analyzed the psychometric properties of the scale, applied to a sample of 378 students of the Faculty of Education at the University of Cordoba. The scale consists of 13 items, divided into three dimensions of the process of identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
(39 reference statements)
4
8
0
Order By: Relevance
“…In a sample including undergraduate students from 10 nations (n = 6118), Crocetti et al (2015) investigated the factor structure of the U-MICS in education and found that commitment was positively correlated with in-depth exploration (r = .50); commitment was negatively correlated with reconsideration of commitment (r = À.32); and in-depth exploration was not related to reconsideration of commitment (r = À.07). A similar pattern of factor correlations was found in studies focusing on global identity (education and relational) for undergraduate students in France (Zimmermann et al, 2012) and Spain (Llorent & Alamo, 2018): commitment was positively related to in-depth exploration (r = .43-.75); commitment was negatively related to reconsideration of commitment (r = À.26 to À.20); and in-depth exploration was not related to reconsideration of commitment (r = À.06 to .04).…”
Section: The U-micssupporting
confidence: 80%
See 3 more Smart Citations
“…In a sample including undergraduate students from 10 nations (n = 6118), Crocetti et al (2015) investigated the factor structure of the U-MICS in education and found that commitment was positively correlated with in-depth exploration (r = .50); commitment was negatively correlated with reconsideration of commitment (r = À.32); and in-depth exploration was not related to reconsideration of commitment (r = À.07). A similar pattern of factor correlations was found in studies focusing on global identity (education and relational) for undergraduate students in France (Zimmermann et al, 2012) and Spain (Llorent & Alamo, 2018): commitment was positively related to in-depth exploration (r = .43-.75); commitment was negatively related to reconsideration of commitment (r = À.26 to À.20); and in-depth exploration was not related to reconsideration of commitment (r = À.06 to .04).…”
Section: The U-micssupporting
confidence: 80%
“…Consistent evidence has supported the three-dimensional model of identity formation, including commitment, indepth exploration, and reconsideration of commitment among undergraduate students (Crocetti et al, 2015;Llorent & Alamo, 2018;Zimmermann et al, 2012). In a sample including undergraduate students from 10 nations (n = 6118), Crocetti et al (2015) investigated the factor structure of the U-MICS in education and found that commitment was positively correlated with in-depth exploration (r = .50); commitment was negatively correlated with reconsideration of commitment (r = À.32); and in-depth exploration was not related to reconsideration of commitment (r = À.07).…”
Section: The U-micsmentioning
confidence: 86%
See 2 more Smart Citations
“…Both questionnaires are self-report tools and enable measuring identity processes in various domains. The U-MICS questionnaire was validated in various countries and cultures, such as: Bulgaria, Czech Republic, China, Greece, Italy, Japan, Kosovo, the Netherlands, Poland, Portugal, Romania, Slovenia, Switzerland, Taiwan, and Turkey (see: Crocetti et al, 2015;Dimitrova et al, 2015, Llorent & Alamo, 2018. Inspired by the three-factor model and U-MICS questionnaire, modified the original U-MICS scale by adding bi-directional scoring to the commitment subscale and including eight identity domains previously identified in qualitative studies to be the most important for identity in emerging adulthood -the number of items per domain was unchanged.…”
Section: Figure 1 Two Cycles Of Identity In Two Conceptualizationsmentioning
confidence: 99%